Imaging phonon-mediated hydrodynamic flow in WTe2 - Vool, Uri; Hamo, Assaf; Varnavides, Georgios; Wang, Yaxian; Zhou, Tony X.; Kumar, Nitesh; Dovzhenko, Yuliya; Qiu, Ziwei; Garcia, Christina A. C.; Pierce, Andrew T.; Gooth, Johannes; Anikeeva, Polina; et al. (Nature Physics, 2021)
In the presence of interactions, electrons in condensed-matter systems can behave hydrodynamically, exhibiting phenomena associated with classical fluids, such as vortices and Poiseuille flow1–3. In most conductors, electron–electron interactions are minimized by screening effects, hindering the search for hydrodynamic materials; however, recently, a class of semimetals has been reported to exhibit prominent interactions4,5. Here we study the current flow in the layered semimetal tungsten ditelluride by imaging the local magnetic field using a nitrogen-vacancy defect in a diamond. We image the spatial current profile within three-dimensional tungsten ditelluride and find that it exhibits non-uniform current density, indicating hydrodynamic flow. Our temperature-resolved current profile measurements reveal a non-monotonic temperature dependence, with the strongest hydrodynamic effects at approximately 20 K. We also report ab initio calculations showing that electron–electron interactions are not explained by the Coulomb interaction alone, but are predominantly mediated by phonons. This provides a promising avenue in the search for hydrodynamic flow and prominent electron interactions in high-carrier-density materials.
CRIS-Team Scopus Importer:2022-04-14